Dengue Hemorrhagic Fever Surveillance System Training And Case Mapping For Dengue Hemorrhagic Fever Program Managers At Community Health Center Level In Bogor City In 2022 - Sinulingga, Iska Beritania (Al Makki Publisher, 2023)
Background: Bogor City has an incidence rate of 21.4 per 100,000 population, but the CFR is quite high at 2.49%. Therefore, it is necessary to increase knowledge about surveillance among DHF program holders in Bogor City in 2022. Method: The study design in this DBD operational research is a non-experimental pre-test and post-test design study. Primary data starts from the results of the pretest-posttest for the DHF program manager using a questionnaire, while mapping skills are taken from the observation sheet that has been made. Meanwhile, secondary data is obtained from the profile analysis results of the Bogor City Health Service. Data analysis was carried out using univariate, bivariate and normality tests. Results: there was a difference in the knowledge of DBD Community Health Center program holders after training in terms of knowledge of DHF surveillance (Pvalue < 0.05). There is a difference in increasing skills in mapping dengue cases among community health center dengue fever program holders after training in mapping using applications (Pvalue < 0.05), and there is an increase in interpreting data and determining regional stratification of dengue cases (Pvalue < 0.05 ) Conclusion: increasing the knowledge and skills of dengue program holders is carried out using appropriate interventions, so that dengue program holders can implement a good surveillance system in preventing and controlling dengue fever